Diabetic Ketoacidosis Without Diabetes Mellitus in Acute Pancreatitis - Duha Zaffar, MD; Aditi Rawat, MD; Robert T. Chow, MD; Kashif M. Munir, MD (AACE Clinical Case Reports)
Background/Objective: Diabetic ketoacidosis (DKA) is typically but not exclusively seen in patients with a history of diabetes mellitus. Case Report: This is a case of 39 year-old male who was diagnosed with acute pancreatitis based on characteristic symptoms and positive CT findings on presentation. Laboratory testing revealed elevated serum glucose 251 mg/dL, low serum bicarbonate 8 mmol/L, increased anion gap 21, and elevated serum beta-hydroxybutyrate 9.62 mmol/L. Diagnosis of DKA was made, however patient did not carry a diagnosis of diabetes mellitus. His hemoglobin A1c in hospital was normal at 5.4%. Additionally, follow-up hemoglobin A1c at 4 months and 10 months postdischarge did not imply diabetes mellitus, 5.8% at both time points. The patient who was initially managed with intravenous insulin required no insulin or oral diabetic medication on discharge. All these findings argued against new onset diabetes mellitus. Discussion: This case explores the potential pathophysiology that underlies this phenomenon including possible transient insulin insufficiency due to beta cell dysfunction from pancreatic inflammation. It also highlights the reversibility and transiency of possible beta cell dysfunction during acute pancreatitis and emphasizes the importance of closely assessing the patients' insulin requirements upon discharge, especially when a prior history of diabetes mellitus is absent. Conclusion: DKA can occur as a rare complication of acute pancreatitis in a nondiabetic patient. Hyperglycemia associated with acute pancreatitis-induced DKA can be temporary and these patients might not necessarily require insulin upon discharge. Therefore, careful discharge planning is very important in such patients.